Neurophysiological correlates of interpersonal discrepancy and social adjustment in an interactive decision-making task in dyads - Vicente, Unai; Ara, Alberto; Palacín-Lois, María; Marco-Pallarés, Josep (Frontiers in Psychology, 2024)
The pursuit of convergence and the social behavioral adjustment of conformity are fundamental cooperative behaviors that help people adjust their mental frameworks to reach a common goal. However, while social psychology extensively studies conformity by its influence context, there is still plenty to investigate about the neural cognitive mechanisms involved in this behavior. We proposed a paradigm with two phases, a pre-activation phase to enhance cooperative tendencies and, later, a social decision-making phase in which dyads had to make a perceptual estimation in three consecutive trials and could converge in their decisions without an explicit request or reward to do so. Study 1 showed behavioral evidence from 80 participants that the pre-activation phase enhanced convergence in dyads. In Study 2, we registered in phase 2 the electroencephalographical (EEG) activity of 36 participants. Event-related Potentials (ERP) revealed signal differences in response divergence in three intervals. Time-frequency analysis showed theta, alpha, and beta evidence related to cognitive control, attention, and reward processing associated with social convergence.